Pengaruh Kadar Abu Gosok Selama Perebusan Dan Lama Perendaman Air Terhadap Kadar Tanin Buah Dan Tepung Mangrove (Avicennia marina) - Perdana, Yanuar Sandy; Soenardjo, Nirwani; Supriyantini, Endang (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Mangrove fruit has the potential to be developed as a potential food source, but the presence of toxins in the fruit are considered harmful if consumed in the long run. Therefore, research needs to be done to eliminate or reduce the levels of toxins in the mangrove fruit, The poison in one of which is the fruit of mangrove tannins. One alternative to reduce the levels of toxins in the fruit of the mangrove scrub with ash and water immersion. This research used Completely Randomized Design, factorial pattern consisting of two factors with three replications, factor I was rubbing ash powder content (5%, 10%, and 15%), and factor II is long soaking water for 6 hours (with 4, 8, 12 times the turnover of water). The results showed that treatment with boiling some rubbing ash content (5%, 10%, and 15%) and long soaking water to give a significant influence (P <0.05) toward decreased levels of mangrove Avicennia marina fruit tannins. Treatment of boiling ash content of 15% gave the lowest reduction is 28.92% and the long soaking water for 6 hours with a change of water 12 times giving the low tannin levels decrease is 28.80%, as well as mangrove fruit flouring will A.marina lower levels of tannin by 28.44%.